Modified Trampoline / Mohd Fahmi Aluwi … [et al.] - Aluwi, Mohd Fahmi; Azman, Abdul Latif; Baharuddin, Muhammad Amiruddin; Japri, Muhammas Izzat; Haron, Rohani (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
Trampoline has been widely used in rehabilitation such as in ACL reconstruction. The ideas on innovation of trampoline for rehabilitation come from students' observation during their clinical placement at the government hospitals. Here, they had identified the lack of safety measure especially when the trampoline is placed near to the wall with no hold onto. Patients with balance problem primarily with have greater risk of injury due to less in joint proprioception and lead to excessive bouncing. So, the new concepts introduced by the students are portable trampoline and also provided with handle so that patients can place their hands to prevent fall and to gain confident during exercise thus acting as precautions. Where rehabilitation is concerned, Physiotherapists have indicated that the effectiveness in using trampoline for exercise is an issue because the tension of the springs cannot be modified. The tension is fixed meaning that it could be dangerous to patients in acute stage where the bouncing effect will further worsen the injury. Besides, the progression of exercise is limited as we cannot see from the initial stage up to final stage of rehabilitation. Therefore, the new concepts introduced in innovation of trampoline are resistance and support. With the adjustable springs, handles and base, the trampoline becomes more users friendly. Hence, trampoline-related injuries can be minimized and prevented.